PERAN PEMERINTAH KABUPATEN/KOTA DALAM PENGAWASAN KEGIATAN PERTAMBANGAN DI WILAYAHNYA: The Role Of The Regency/City Government In Supervising Mining Activities In Their Area - Serasi Floria Silaban; Meta Indah Budhianti (Reformasi Hukum Trisakti, 2025)
Regency or city governments have an important role in supervising mining activities in accordance with the Regional Government Law and the Mineral and Coal Law. However, with the enactment of the new Minerba Law, this role has undergone significant changes. This research aims to analyze the role of district or city governments in mining supervision before and after the enactment of the new Minerba Law, which revoked some regional authorities. The research results show that previously, regional governments had the authority to grant permits and supervise mining activities. However, with the presence of the new Minerba Law, this authority shifted to the central government, causing district/city governments to lose most of their responsibilities. However, local governments still play a role in aspects of environmental monitoring and law enforcement at the local level.